Bangladesh, rural infrastructure strategy study - World Bank. SA1 Infrastrucutre Division; Bangladesh. Local Government Engineering Dept.; Bangladesh. Parikalpanā Kamiṣana. Rural Infrastructure Development Wing. (Dhaka : Published for the World Bank by University Press, 1996)
Report of seminars held in Dhaka during 1994 & 1996.
Includes bibliographical references (p. [109]-111).
Keywords: Infrastructure (Economics) -- Bangladesh; Rural development -- Bangladesh; Bangladesh -- Politics and government